2023
DOI: 10.1088/2634-4505/acf60d
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-scale air quality, public health, and equity implications of multi-modal vehicle electrification

Maxime A Visa,
Sara F Camilleri,
Anastasia Montgomery
et al.

Abstract: Electric vehicles (EVs) constitute just a fraction of the current U.S. transportation fleet; however, EV market share is surging. EV adoption reduces on-road transportation greenhouse gas emissions by decoupling transportation services from petroleum, but impacts on air quality and public health depend on the nature and location of vehicle usage and electricity generation. Here, we use a regulatory-grade chemical transport model and a vehicle-to-electricity generation unit electricity assignment algorithm to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Our use of census tract pollutant and health data enables us to capture wider and more representative variability in underlying population subgroup susceptibilities and associated disparities in NO 2 mortality burdens, a result which would otherwise be underrepresented if using county-, state-, or national-level data . Our results indicate that policies aimed at reducing NO x emissions such as those pertaining to the transportation sector , could reduce long-standing environmental injustices and motivate more stringent air quality standards.…”
Section: Discussionmentioning
confidence: 93%
“…Our use of census tract pollutant and health data enables us to capture wider and more representative variability in underlying population subgroup susceptibilities and associated disparities in NO 2 mortality burdens, a result which would otherwise be underrepresented if using county-, state-, or national-level data . Our results indicate that policies aimed at reducing NO x emissions such as those pertaining to the transportation sector , could reduce long-standing environmental injustices and motivate more stringent air quality standards.…”
Section: Discussionmentioning
confidence: 93%
“…Further, the consensus hotspot comprises an area that is majority Hispanic or Latino (54%; tables S1 and S2). Although the estimates from each data product, separately, are subject to concerns regarding potential sources of bias and noise, the consistency of results across data sources as well as the urgency of EJ-related health inequities suggests that this area should be prioritized for clean air interventions (Camilleri et al 2023, Visa et al 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the potential for vehicle electrification to have significant air quality and health benefits. In particular, electrification of heavy-duty diesel vehicles, which are less efficient and more polluting than light-duty vehicles, is expected to reduce air pollution and health impacts in some regions [31][32][33]. However, in regions with significant coal generation, electrification may result in an increase in air quality and health damages.…”
Section: Air Quality and Health Equitymentioning
confidence: 99%